Prototype application for curtain calculator / Nurul Aznizam Mohamed Zaman - Mohamed Zaman, Nurul Aznizam (2010)
Prototype Application For Curtain Calculator is to solve the problem and also to determine solution for arrangement of designing and calculating the exact measurement and also estimation of the curtain. This prototype is to develop a system using simple arithmetic to calculating the exact measurement in terms of estimation, measurement and budgeting that involve various design and fabric of required. This prototype will calculate the amount of fabric that will be required based on each curtain design and will calculate the cost that will be budgeting to make a curtain. In order to calculate the amount of fabric of each curtain design, all the data had been gathered from a small medium enterprise and tailors. This project methodology consists of five stages which are prototype requirement analysis, prototype design, prototype development,prototype testing and implementation. Each phases of the research methodology was gone through in order to complete this project and analyze the effectiveness of the prototype. The accuracy of this prototype is about 60 percent. The project is a prototype application and has been developed using PHP as programming language and PhpMyAdmin as database tool.